Juridical Review of The Criminal Actions Performed by Children Against Children by Doing Deception and A Series of Lies (Decision Study Number 17/Pid.Sus-Children/2022/Pn Pwt) - Arvina Nur Febriana Putri (UM Purwokerto Press, 2023)
The development of the world in this era of globalization shows a very rapid development, marked by positive influences, namely more advanced and developed science and technology. In addition to the positive effects that have been received, there have also been many negative effects that have also been received from globalization, in which crime has become more developed and sophisticated both in terms of quantity and quality. Along with the development of the era of globalization, there are also many crimes committed by children, which causes public concern. Crimes committed by these children include rape, obscenity, sexual abuse and sexual acts.. In this research, the problem to be solved is how to consider the decision of the judge issued to the child, from the point of view of restorative justice. The purpose of it is to find out the grounds for sentencing children in the order of restorative justice as a form of settlement of the crime of sexual intercourse committed by a child against a child. The authors used empirical legal and regulatory research with reference to the theoretical nature of the provisions of the applicable law and field research to establish facts about specific legal developments. In this research, the authors use the case approach method. The results of this research will be useful for the development of legal science, in particular to increase knowledge and add references, especially on issues related to the use of punishment against children in Indonesia, especially in cases of child-on-child sexual intercourse.